Effect of Local Cold Injury on Osmotic Resistance of Erythrocytes - Chabanenko, Olena O.; Kovalov, Gennadiy O.; Iefimova, Inessa A. (Problems of Cryobiology and Cryomedicine, 2019)
Probl Cryobiol Cryomed 2019; 29(2): 168.